TYPES OF HOUSES FOR PROTECTION FROM MUDFLOWS FOR LIVESTOCK BREEDERS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article describes in detail the mountainous and watery nature of Kyrgyzstan, its natural beauty and four seasons. It also describes flood-resistant houses for livestock farmers. Advantages and disadvantages of the houses under consideration. The economic advantages of these houses are shown. Sensors that determine the flood level are given and the types of sensors are described.It was stated that it is possible to create a device that determines the rise in water level using sensors.The most important thing is that the house-lifting devices are installed in such a way that they can lift the house inside the pipes dug into the ground.These houses are also powered by solar energy. This is economically beneficial for livestock farmers. Livestock will not die or be washed away by floods.
Keywords: Animals, creatures, floods, submergence, floating, Archimedes force, friction force, lifting force, weight, gravity, volume, mass, density, traction force, sensors, jack (lifting device)